METHODOLOGICAL CONCEPT OF DEVELOPMENT OF PROJECT CULTURE OF VOCATIONAL EDUCATION TEACHERS (Innovative professional education, 2023)
This paper highlights the methodology for developing professional standards for training skilled workers in the service sector. It discusses the labor functions of the cosmetologist, manicurist, and pedicurist professions. The paper also provides a rationale for the seven stages of developing professional standards in the service sector: the first stage involves preparation, the second stage involves analyzing professional activities by profession, the third stage involves forming a list of labor functions, the fourth stage involves determining the competencies required to perform the labor functions, the fifth and sixth stages involve determining learning outcomes, and the seventh stage involves distributing labor functions among professional qualifications.